Acute Liver Failure Secondary to Metastatic Medullary Thyroid Cancer - Emmanuel C. Gorospe; Jemilat Badamas (Case Reports in Hepatology)
Acute liver failure (ALF) is a rare presentation of liver metastases. Although cases of ALF from metastatic disease have been reported, etiologies have been largely confined to lymphoma, metastatic breast, lung, and gastric cancers. ALF from medullary thyroid cancer (MTC) has never been reported. We present a 59-year-old male with newly diagnosed MTC, who was admitted with ALF. He presented with jaundice, hepatic encephalopathy, and synthetic dysfunction. His clinical course was marked by rapid decompensation within 6 days from initial presentation of jaundice to development of hepatic coma. Although liver metastases from medullary thyroid cancer have been reported, to our knowledge, this is the first described case of MTC resulting in acute liver failure.